Instilling Faith and Morals in Early Childhood - Bustamam, Mutia (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
The instillation of faith (aqidah) and morals (akhlaq) in early childhood is a strategic step in shaping strong Islamic character, especially in response to the challenges of the modern era. This study aims to examine an integrative approach involving families, schools, and digital media in embedding the values of aqidah and akhlaq in children. Using a qualitative research method based on literature review, this study reveals that early childhood is a golden period where children possess exceptional abilities to absorb positive values. The findings indicate that synergy between families, formal education, and digital media supervision is the key to addressing modernization challenges that often contradict religious values. This study also highlights the importance of wisely utilizing digital media as a supportive tool to reinforce Islamic values. The research contributes by offering practical and relevant strategies to support the development of Islamic character in early childhood through a holistic and integrated approach.